Inovasi Peningkatan Mutu Pembelajaran Agama Hindu Yang Kontekstual - I Nyoman Kiriana (UHN IGB Sugriwa Denpasar, 2018)
Religious learning in the era of technology and information will experience many obstacles in the realization if not accompanied by a contextual learning model. Teachings delivered will be more successful if delivered by forming aspects of sense and aspect ratio that can be accepted with common sense. Thus in the learning of religion should make the maximum innovation adjusted with space and time and in tune with the changes and development of the era. Utilization of information technology is very important in the learning of Hinduism for learning purposes can be achieved in accordance with expectations